All-in-one nursing care planning resource medical-surgical, pediatric, maternity, psychiatric nursing care plans - Swearingen, Pamela L. (Elsevier/Mosby, 2019)
Features nursing care plans for all four core clinical areas. This unique presentation makes this a must-have care plans book for nursing students